Artistic Portrait of Mental State of Human "Baburname" (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article is given analysis of Babur's overview, his points on social-political situation of that time, being master of poet in using words and expressions, his abilities to reveal social-political situation of that time through psychology of winner and being winner by prisms of his abilities in terms of history, politics and impartial expert.